DIALEKTIKA AGAMA DAN BUDAYA - Poniman Poniman (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
Religion  as  divine  guidance was  revealed to humans who  have  had  culture.  While  the  culture  is essential in the life of a society, as a society however simple,  still have a work culture,  ethics  and taste.  When religion comes to this locus there was a dialectic between the two. This dialectic bore variant-variant  in religion ie Islam Indonesia, Islam Morocco and so on. More specifically, when the religion (Islam) dialectic with the local culture  (local  wisdom) will form a distinctive  variant of Islam such  as: Islam Madura, Islamic Javanese, Malay Muslims and  so on. This variant does  not mean that religion has  been deprived of its purity, but religion was dialectic with culture